Biological weapon as a tool in the process of reducing the structural power of a state - Chabska Katarzyna (2024)
The purpose of this article is to present biological weapon in the process of reducing the structural power of a state. This article answers the following questions: What is the structural power and national economy? What is human capital and agriculture? What is the biological weapon and what is its effectiveness? How does the biological weapon reduce the structural power of a state?